Penerapan Manajemen Risiko Perusahaan dan Nilai Perusahaan di Sektor Konstruksi dan Properti - Oka Aditya; Prima Naomi (Esensi: Jurnal Bisnis dan Manajemen, 2017)
Implementation of Enterprise Risk Management and Firms' Value at Construction and Property SectorsThe objective of this study is to emphasize the effect of enterprise risk management (ERM) and control variable i.e: firm size, leverage, profitability, sales growth, shares volatility, and dividend policy toward firm value. This research employs multiple regressions as tool of analysis. The object of this research is construction and property firms that listed on BEI in period 2012-2014. The result of this research showed that ERM and control variable have a significant effect on firm value. However, partially, ERM doesn’t have significant effect on firm value. Further more leverage and sales growth variable have significant effect on firm value. The other funding is that size, leverage and dividend policy have significant correlation on ERM.DOI: 10.15408/ess.v7i2.4981